2014
DOI: 10.3389/fpsyg.2014.00458
|View full text |Cite
|
Sign up to set email alerts
|

Children’s giving: moral reasoning and moral emotions in the development of donation behaviors

Abstract: This study investigated the role of moral reasoning and moral emotions (i.e., sympathy and guilt) in the development of young children’s donating behavior (N = 160 4- and 8-year-old children). Donating was measured through children’s allocation of resources (i.e., stickers) to needy peers and was framed as a donation to “World Vision.” Children’s sympathy was measured with both self- and primary caregiver-reports and participants reported their anticipation of guilt feelings following actions that violated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
1
50
1
2
Order By: Relevance
“…Finally, future research should investigate differences in quality equality across different kinds of participants and recipients (e.g., varying in relationship, need, and merit). For example, previous research has sometimes found gender differences in prosocial behavior, with many studies finding higher prosocial behavior in girls than in boys (e.g., Ongley, Nola, & Malti, )—though other studies find the opposite (e.g., Derks, Lee, & Krabbendam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future research should investigate differences in quality equality across different kinds of participants and recipients (e.g., varying in relationship, need, and merit). For example, previous research has sometimes found gender differences in prosocial behavior, with many studies finding higher prosocial behavior in girls than in boys (e.g., Ongley, Nola, & Malti, )—though other studies find the opposite (e.g., Derks, Lee, & Krabbendam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such sharing behavior has been related to the ability to sympathize with anonymous others (Malti, Gummerum, Keller, Chaparro, & Buchmann, ) and to children's emotional attribution in response to moral transgressions (Gummerum, Hanoch, Keller, Parsons, & Hummel, ). Children's need‐based donating behavior is predicted by their moral reasoning capacities (Ongley, Nola, & Malti, ). The prominence of distributive fairness considerations in childhood motivates asking whether more basic roots of fairness expectations might even be detected in infancy and, if so, whether their development is linked to specific attributes indicative of infants’ early moral understanding.…”
Section: Children's Fairness Concerns and Moral Developmentmentioning
confidence: 99%
“…review several studies showing that children under the age of 8 years are poor at predicting negative self-evaluation when the outcome for self is 28 superficially positive (such as when one gains chocolate by stealing). The switch to 'mature' prediction of self-evaluative emotion is associated with an increase in sharing and altruism (Malti & Krettenauer, 2013;Ongley, Nola & Malti, 2014). Without the current study, one might conclude from this pattern that young children's experiences of self-evaluative emotion are nascent, and not related to the same antecedents and consequences as adult emotions.…”
Section: Discussionmentioning
confidence: 66%
“…Such results have led Kochanska and colleagues to consider guilt the 'motivational engine' of a social conscience (Kochanska & Askan, 2006, p.1589. Later in childhood, positive associations between the capacity to predict guilt in Self-evaluative emotion and preschool prosociality 8 hypothetical scenarios and the tendency to make prosocial choices have also been reported (Chapman et al, 1987;Koenig, Cicchetti, & Rogosch, 2004;Malti & Krettenauer, 2013;Ongley, Nola & Malti, 2014). However, the developmental literature linking the onset of self-evaluative emotional experiences with developmental changes in prosociality is surprisingly limited not only in size, but in scope.…”
mentioning
confidence: 99%